POLA KECENDERUNGAN PENANGKAPAN BURUNG-BURUNG LIAR BERNILAI EKONOMIS DAN IMPLIKASI KONSERVASINYA: STUDI KASUS DITANAH GROGOT, KABUPATEN PASER, PROVINSI KALIMANTAN TIMUR - Rachmat Budiwijaya Suba; Aditya Rakhman; Rustam Rustam (BERITA BIOLOGI, 2011)
The study aims at quantifying trade scale of some economically wild birds and describing captured trends which have been practised by wild bird catchers. The study was conducted in Tanah Grogot, Paser District, East Kalimantan Province, from September to December 2008, by surveying wild bird market and interviewing catchers and sellers. We measured two main attributes of market dynamics; first, each species availability in the market as the percentage of market days sampled where the species appeared; second, daily abundance of a species as the monthly average number of each bird per day for all days sampled. Seven wild bird species that have been traded commodities for years were White-rumped Shama Copsychus malabaricus (25.41%; 602.25+70.79 individuals per month), Yellow-vented Bulbul Pycnonotus goiavier (11.47%; 111.25+12.50 individuals per month), Crested Myna Acridotheres cristatellus (12.30%; 73.25+10.44 individuals per month), Spotted Dove Streptopelia chinensis (5.73%; 22.00+12.83 individuals per month), Hill Myna Gracula religiosa (12.30%;12.00+0.82 individuals per month), Greater Green Leafbird Chloropsis sonneratii (7.38%; 11.75+2.50 individuals per month) and Magpie Robin Copsychus saularis (6.56%; 8.75+1.71 individualsper month). Specific capture location within Paser District could reflect distribution and habitat preference of each bird species.